2016
DOI: 10.1002/14651858.cd003733.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled bronchodilators for acute chest syndrome in people with sickle cell disease

Abstract: If bronchial hyper-responsiveness is an important component of some episodes of acute chest syndrome in people with sickle cell disease, the use of inhaled bronchodilators may be indicated. There is need for a well-designed, adequately-powered randomised controlled trial to assess the benefits and risks of the addition of inhaled bronchodilators to established therapies for acute chest syndrome in people with sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The high variability we found in the use of bronchodilators for ACS likely reflects the dearth of published evidence regarding their efficacy in the SCD population 18 as well as conflicting expert recommendations. Some authors suggest using bronchodilators only in patients with a known history of asthma or as a trial in those who are wheezing on physical examination, 20 while others recommend that AHR should be assumed to be present in all patients and bronchodilators should be used universally.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The high variability we found in the use of bronchodilators for ACS likely reflects the dearth of published evidence regarding their efficacy in the SCD population 18 as well as conflicting expert recommendations. Some authors suggest using bronchodilators only in patients with a known history of asthma or as a trial in those who are wheezing on physical examination, 20 while others recommend that AHR should be assumed to be present in all patients and bronchodilators should be used universally.…”
Section: Discussionmentioning
confidence: 96%
“…Our results show that bronchodilator use is associated with a modest increase in length of hospital stay for patients admitted with ACS. It is possible that the adverse effects of bronchodilators such as tachycardia, anxiety, and hyperactivity 18 may be contributing to a longer length of stay. In subgroup analysis, we found that length of stay was increased with bronchodilator use among subjects who did not have a co-diagnosis of asthma; however, in subjects with a co-diagnosis of asthma, bronchodilator use was associated with a decreased length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane reviews by Knight-Madden and colleagues have not identified a single article regarding albuterol and SCD. 58,59 …”
Section: Management Of Wheezing In Scd: Chronic Wheezementioning
confidence: 99%
“…Long term, patients may be placed on an inhaled corticosteroid or leukotriene receptor antagonist 11,12,20,29 . The physiologic benefit of albuterol has been demonstrated in the literature, as patients with SCD have higher rates of asthma, airway hyperreactivity, and bronchodilator responsiveness 8,2,16,30 . Inhaled corticosteroids are another mainstay of asthma treatment, and otherwise healthy children with asthma are more likely to have a controller prescription after pediatric pulmonary consultation 22 , but not many studies have been performed in the SCD population.…”
Section: Discussionmentioning
confidence: 99%